New Zealand : Selected Issues. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper analyzes the underlying factors that explain the behavior of the Kiwi dollar. The findings suggest that the factors influencing the New Zealand dollar have been changing. The paper discusses that as New Zealand has become more integrated in global capital markets over time, the Kiwi dollar has become less of a commodity currency and more of a global currency that is influenced by interest rate spreads and global risk factors. The paper also looks at the strong preference for housing over financial assets exhibited by New Zealand households.